2018
DOI: 10.1097/hcr.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Blockers on Maximal Heart Rate Prediction Equations in a Cardiac Population

Abstract: For patients holding BB therapy on test day, a similar CAD HRmax estimation equation to those patients never on BB can be used, comparable to the Brawner (no BB) equation. Further research is needed to determine when patients should take their BB therapy in conjunction with exercise testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…[22]. Where a participant was prescribed a beta‐adrenergic blocking agent, an equation in patients with coronary artery disease was used to estimate predicted maximum heart rate [23]; no predictive equations for healthy older adults or individuals with osteoarthritis are available. Prism (v8.0; GraphPad Software, CA, USA) was used for all statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[22]. Where a participant was prescribed a beta‐adrenergic blocking agent, an equation in patients with coronary artery disease was used to estimate predicted maximum heart rate [23]; no predictive equations for healthy older adults or individuals with osteoarthritis are available. Prism (v8.0; GraphPad Software, CA, USA) was used for all statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The attenuated HR response in this subgroup may underlie this finding. 23 Several previous studies have evidenced a worse prognosis when impaired chronotropic response is confirmed in ExECG. 24 In line with our results, one study of 5437 asymptomatic women found that all-cause mortality risk was reduced by 3% per increased bpm during ExECG after adjusting for traditional risk factors and exercise capacity.…”
Section: Discussionmentioning
confidence: 96%
“…One explanation for this is that antihypertensive drugs, such as beta-adrenergic blockers, may alter baseline heart rate as well as during exercise [37][38][39] . Oxygen saturation values remained within normal limits during all sessions, indicating that EAT is safe for normotensive and hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%